Farm structures and rural electrification palm kernel shells as coarse aggregates for light weight concrete (1999)
The escalating cost of conventional building material has given rise to the need to source for alternative ones. In souring for such alternatives, the durability, availability and cost of the potential material should be considered. Palm kernel shell (PKS), a by-product in the process of palm kernel oil extraction found in abundance in southern and grossly underutilized was considered of potential as a coarse aggregate for light weight concrete. In order to confirm the assumed potential, it was considered necessary to determine the density and compressive strength of concrete cubes manufactured from PKS. Coarse aggregates made us of crushed granite and PKS mixed in varied proportions were used to cast 150mm x 150 mm concrete cubes of 1: 3: 6 mix batch by weight. The cubes were removed from moulds 24hr after casting and immersed in water for seven days to cure. The density and compressive strength of the cubes were then decreased. Expectedly, the density and crushing strength of cubes decreased with increase in the amount of PKS in the cubes but the density range of 1520 to 2234kg/m3 and strength values of 0.44 to 3. 89N/mm2 obtained were good enough for light weight concrete. PKS has great potential as a material for coarse aggregate in concrete work; the use of which could considerably reduce the construction cost of building and promote environmental sanitation.